Assessing extraction trail trafficability using harvester CAN-bus data. Issue 2 (3rd May 2020) - Ala-Ilomäki, Jari; Salmivaara, Aura; Launiainen, Samuli; Lindeman, Harri; Kulju, Sampo; Finér, Leena; Heikkonen, Jukka; Uusitalo, Jori
ABSTRACT: Modern forest machines with a Controlled Area Network (CAN)-bus managed diesel engine and hydrostatic transmission can continuously measure power expended in traveling. At a constant speed on level ground, the power is expended in overcoming motion resistance, which is directly related to wheel sinkage and hence to site trafficability. In cut-to-length timber harvesting, the harvester precedes the forwarder on the site, making it feasible to utilize the harvester to collect data on site trafficability to produce a trafficability map for the forwarder. CAN-bus trafficability mapping was tested with an 8-wheeled Ponsse Scorpion King harvester and an 8-wheeled Ponsse Elk forwarder instrumented for collecting transmission power expenditure, in addition to appropriate available CAN-bus information. Trafficability was also mapped based solely on momentary engine power in order to eliminate the need for additional pressure transducers. The CAN-bus data showed good results for mapping site trafficability when compared to soil penetration resistance and harvesting machinery wheel rut depth measurements. Assessing harvester rolling resistance using CAN-bus data offers an interesting possibility to map harvesting site trafficability also in Big Data scale. Since modern harvesters are practically ready for indirect power recording, the additional cost of fully automated and comprehensive trafficability mapping as part of operative forestry is negligible.